GAMBARAN PENGETAHUAN DAN POLA KONSUMSI WANITAUSIA SUBUR (WUS) - moda, antonia; saleh, asmulyati s; Mali, Alberth M.S Bau (Poltekkes Kemenkes Kupang, 2024)
Women of childbearing age (WUS) are women who are in their late teens to early adulthood. The main characteristics of WUS are characterized by physiological events, such as menstruation and reaching peak fertility with well-developed reproductive organ function. WUS is assumed to be an adult woman who is ready to become a mother. Nutritional needs during this period are different from those of childhood, adolescence or old age. The need for nutrients during this period is important because it is a time to prepare for pregnancy and breastfeeding. For this reason, women are obliged to maintain their health, especially their activities and diet. Diet is a description that informs the number of types and frequency of food consumed every day. Insufficient knowledge of nutrition will cause health problems that affect women's fertility. The results of the analysis stated that there was no relationship between knowledge and consumption patterns and the incidence of SEZ in WUS. This research aims to determine the knowledge and consumption patterns of women of childbearing age. This research is a quantitative research with a Cross Sectional data analysis approach used, namely the Fisher Exact Test. Based on the research results, it is known that the knowledge of women of childbearing age at KUA Kelapa Lima is in the good category 51.4%, sufficient, 37.5% and 11.1% less. The consumption pattern of women of childbearing age in the good category for types of food is 23.6% less than 76.4%, frequency of good food is 58.3%, less than 41.7 %, and total protein intake less 63.9% good 23.6% more 12.5% , fat intake less 79.2% good 8.3% more 12.5% carbohydrates less 70.8% good 18.1% 11.1%.